Analysis of Total Polyhenolic Content and Antioxidant Activity from n-hexane, Ethyl acetate and Ethanol Extract of Kitolod (Hipobbroma longiflora) Leaf - Situmeang, Boima; Faradin, Faradin; Susvira, Dian; Bialangi, Nurhayati; Widiyanto, Holisha; Yulianti, Nani; Jinanti, Nazwa (Jurnal Penelitian Sains, 2025)
Isotoma longiflora, commonly known as Kitolod, has been traditionally used as a medicinal plant for treating various ailments. This study aims to extract Kitolod leaves using three different solvents with varying polarities: n-hexane (non-polar), ethyl acetate (semi-polar), and ethanol (polar). The total phenolic content, total flavonoid content, and antioxidant activity were analyzed using a spectrophotometer. The trends observed in both TFC and TPC results indicate that ethyl acetate is the most effective solvent for extracting bioactive compounds from Kitolod leaves. The ethyl acetate extract of Kitolod leaves exhibited the highest antioxidant activity (150.542 ± 3.917 ppm), followed by the ethanol (157.235±0.858 ppm) and n-hexane (217.345 ± 1.749 ppm) extracts. This suggests that ethyl acetate is the most effective solvent for extracting bioactive compounds with antioxidant properties from Kitolod leaves.